1978
DOI: 10.1063/1.90243
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium enrichment by cw CO2 laser-induced reaction of methane

Abstract: A cw CO2 laser is used to vibrationally excite CH2D2. Intentional VT deactivation competes with interisotope VV transfer and prepares a sample of gas in which the CH2D2 is excited while the CH4 remains unexcited on a steady-state basis. Subsequent reaction of this mixture with chlorine atoms and molecules forms a stable product, deuterated methyl chloride, enriched in deuterium by up to 72%. Extension to the CH3D system will be discussed. A conservative estimate of the energy requirement for a commercial facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Overall case 4 yields a better fit to the thermal rate constant and KIE data than the other cases, but the agreement is only marginally better than for case 5 for which the contribution to the rate constant from the bending mode is neglected. Given that several studies have suggested that low-frequency bending modes enhance the reactivity, , we assume case 4, which includes such contributions, provides the most realistic representation of this system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall case 4 yields a better fit to the thermal rate constant and KIE data than the other cases, but the agreement is only marginally better than for case 5 for which the contribution to the rate constant from the bending mode is neglected. Given that several studies have suggested that low-frequency bending modes enhance the reactivity, , we assume case 4, which includes such contributions, provides the most realistic representation of this system.…”
Section: Discussionmentioning
confidence: 99%
“…These latter studies indicate that CH 4 with energy in the umbrella and torsional modes may be more reactive than CH 4 with energy in the stretch mode. Earlier work by Hsu and Manuccia suggested that exciting the CH 2 rocking mode (υ 7 ) of CH 2 D 2 significantly enhances the reaction rate, whereas experiments by Vijin et al and Chesnokov et al indicated that neither pumping the umbrella mode of CD 4 nor exciting the umbrella or torsional modes of CH 4 enhances the reaction rate significantly. Vibrational enhancement of the reaction probability is indicative of a late barrier along the reaction coordinate on the PES, for which the transition state resembles the products more than the reactants.…”
Section: Introductionmentioning
confidence: 98%
“…Earlier work by Hsu and Manuccia indicated that pumping the CH 2 rocking mode (ν 7 ) of CH 2 D 2 enhances the reaction rate with Cl. In contrast, Vijin et al noted no enhancement in reactivity when directly pumping the umbrella bending mode of CD 4 in a mixture of CH 4 and CD 4 and measuring the isotopic fractionation of products.…”
Section: What Is Known About CL + Ch4mentioning
confidence: 99%
“…Assuming that both the stretching and bending modes of CH 4 enhance the reaction probability for Cl + CH 4 , , the description of the rate constant by eq 2 must contain at least three terms, each of which is characterized by a distinct P rxn ( E coll , ν i ). Figure shows a fit of eq 2 to the absolute rate constants measured for Cl + CH 4 , with one term representing the nearly isoenergetic symmetric and asymmetric stretching modes, one term representing the umbrella bend mode, and one term representing the ground-state and torsional mode, which was assumed not to couple strongly to the reaction coordinate .…”
Section: Dynamics → Kinetics:  Vibrational Enhancement and Non-arrhen...mentioning
confidence: 99%
“…Experimental verification has been lacking in part because selective preparation of low-frequency modes has proven difficult. The few experimental measurements [12][13][14][15][16] that probe the effects of bend excitation on the Cl + CH 4 reaction have been performed using indirect methods, leading to disparate results. Early studies [12] showed no enhancement from the bending mode, whereas more recent measurements [14,15] estimate the enhancement factor to be approximately 200 or approximately 3, respectively, based on studies of residual bend-excited methane present in their molecular beam.…”
mentioning
confidence: 99%